ROLE OF ISLAM IN PREVENTION OF SMOKING - Hameed, Abdul; Jalil, M. Asif; Noreen, Rozina; Mughal, Iqbal; Rauf, Shaid (Journal of Ayub Medical College Abbottabad, 2002)
Background: Smoking is common all over the world. It is a pandemic pollution. In spite of awareness about its dangerous effects on the health, tobacco companies spend million of dollars on its advertisement and sales promotion. This study tried to see the effect of Islam on prevention of smoking. Methods: The study was carried out on 1000 subjects residing in different localities of Abbottabad. The basic method used was a questionnaire designed specifically to give an idea of the religious status of person and correlate that with their smoking habits. Results: Out of the study group 325 (32.5%) were found to be indulged in different kinds of smoking and we concluded that Islam has a positive effect on smoking prevention.